Sonatas and other piano works, ed. by Bülow, vol. 4 (1891, German/English ed.) - Beethoven, Ludwig van, 1770-1827:::::: (1891)
Volume 4 of the Sonaten und andere Werke für das Pianoforte von Ludwig van Beethoven, from the Instruktive Ausgabe klassischer Klavierwerke (Instructive Edition of Classical Piano Works), Abt. 3, containing the Piano Sonatas opp. 53, 54, 57, 78, 79, 81a, and 90, the Variations, op. 76, the Fantasie, op. 77, and the Polonaise, op. 89, with English translations of the instructive text by J. H. Cornell.